Sistem Informasi Penjualan Produk Berbasis Web dan Penyaluran Donasi Untuk Animal Shelter - Martini; Destari Rahmadani Putri; Agustiena Merdekawati (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
Now these online purchases have become convenience for buyers. Pet shop owners sell food products and other animal-related products using desktop-based programs so that not many people know about the products being sold. Many animal shelters require funds for daily needs and medical care. If the animals are well maintained and healthy, they will be adopted by potential adopters who can care for them. The result of this adoption is one way to obtain funds for fees and other animal care at the shelter. The shop owner also wants to invite shoppers to help abandoned animals by offering donations. This design application is made to sell products needed by animal-based websites, as well as designing donations that will be offered to customers. The donation begins with the purchase of products in the form of pet food and other products. The donations will be distributed to animal shelters that can care for and maintain animal health. Customers can also see the donation bookkeeping based on the expenditure of funds from the donations collected and display animals that have been treated. In the development of this application program made with several stages of software development using the Waterfall Method which will be discussed sequentially according to the stages. As for making this application using the PHP programming language and Javascript, with the CodeIgniter framework, and for the database using MySQL. With the sale of products and web-based donations, this can provide more extensive information about the products being sold and at the same time invite customers to take care of abandoned animals.